Periodontal Treatment Reduces Risk of Adverse Respiratory Events in Patients With Chronic Obstructive Pulmonary Disease: A Propensity-Matched Cohort Study - Shen, Te-Chun (Medicine (Baltimore), 2016)
Treatment of periodontal diseases has been associated with benefit outcomes for patients with chronic obstructive pulmonary disease (COPD). However, no population-based cohort study has been conducted. We evaluated this relationship by retrospective cohort study using a large population data. Using the National Health Insurance claims data of Taiwan, we identified 5562 COPD patients with periodontal diseases who had received periodontal treatment as the treatment group. The comparison group was selected at a 1:1 ratio matched by the propensity score estimated with age, sex, date of COPD diagnosis and periodontal treatment, and comorbidities. Both groups were followed up for 5 years to compare risks of acute exacerbation, pneumonia, and acute respiratory failure. The incidence rates of adverse respiratory events were significantly lower in the treatment group than in the comparison group: 3.79 versus 4.21 per 100 person-years for emergency room visits, 2.75 versus 3.65 per 100 person-years for hospitalizations, and 0.66 versus 0.75 per 100 person-years for intensive care unit admissions. The treatment group also had a 37% reduced risk of deaths (1.81 vs 2.87 per 100 person-years), with an adjusted hazard ratio of 0.57 (95% confidence interval 0.52–0.62). Periodontal treatment for COPD patients could reduce the risk of adverse respiratory events and mortality. The adequate periodontal health care is important for COPD patients with periodontal diseases.